Phase II Study of Abiraterone Acetate Plus Prednisone in Chemotherapy-Naïve Metastatic Castration-Resistant Prostate Cancer Demonstrating Radiographic Flare Discordant With Serologic Measures of Response - Ryan, Charles J. (2011)
PURPOSE: Abiraterone is an oral inhibitor of CYP17, essential for androgen biosynthesis. This multicenter study assessed its efficacy in patients with CRPC without prior exposure to chemotherapy or CYP17 targeted therapy, and assessed the frequency of interpretation of bone scans discordant with PSA and clinical response. PATIENTS AND METHODS: 33 patients received abiraterone acetate 1000 mg daily with prednisone 5 mg twice daily in continuous 28-day cycles. Patients were evaluated monthly for efficacy and safety. Bone scan flare was defined as the combination, after 3 months of therapy, of an interpreting radiologist's report indicating “disease progression” in the context of a ≥50% decline in PSA, with scan improvement 3 months later. RESULTS: A ≥ 50% PSA decline at week 12 was confirmed in 22/33 (67%) patients. PSA declines of ≥ 50% were seen in 26 (79%) patients. Undetectable PSA levels (≤ 0.1 ng/mL) occurred in 2 patients. Median time on therapy and time to PSA progression are 63 and 71 weeks, respectively. Twenty three patients were evaluable for bone scan flare. Progression was indicated in the radiologist's report in 12/23 (52 %), and 10/12 subsequently showed improvement. As prospectively defined, bone scan flare was observed in 10/23 (43.5%) evaluable patients or 10/33 (30%) enrolled patients. Adverse events were typically grade 1/2 and consistent with prior published abiraterone reports. CONCLUSION: Clinical response to abiraterone acetate plus prednisone was frequent and durable in men with metastatic CRPC progressing on hormonal therapy with over half of patients on therapy > 1 year. Further investigation is needed to clarify the potential confounding effect of the frequently occurring bone scan flare phenomena on patient management and interpretation of clinical trial results.